Pengaruh Temperatur Dan Katalis Lempung Aktif Pada Pengolahan Sampah Plastik Jenis Polypropylene Dengan Metode Pirolisis - Shaleh, Idries Hamidi; Daud, Syarfi; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The increasing amounts of plastic wastes generate enormous environmental problems because its nonbiodegradable properties. Various attempts have been done to reduce plastic waste. One of the way to reuse the plastic waste is converted to the liquid fuel by pyrolisis process. Pyrolysis, while can decomposed plastic safely, its product can be alternative source of fuel. The purpose of this study is to observe the effect of process variable (process temperature and active clay catalyst) for yield form polypropylene plastic and generated pyrolysis liquid fuel characterization. The pyrolysis process was carried out at 300 oC, 350 oC, 400 oC and variation of active clay catalyst to 0.5%, 1%, 1.5% and non-catalyst for polypropylene plastic and with reaction time of 120 min. The results of this study resulted in the highest yield of 65.86% at 400oC and 1.5% active clay catalyst. Characterization of pyrolysis liquid fuel of density 0,784 gram / ml, kinematic viscosity 2,956 cSt, flash point 49 oC and caloric value 46,815 MJ/ kg.Keyword : pyrolysis, active clay, polypropylena, pyrolysis liquid fuel